Swallowing outcomes in children after slide tracheoplasty. (May 2018) - Stewart, Alexandra J.; Butler, Colin R.; Muthialu, Nagarajan; Sell, Debbie; Marchant, Joseph; Hewitt, Richard J.D.; Elliott, Martin J.
Abstract: Introduction: Slide tracheoplasty is now considered gold standard treatment for long segment congenital tracheal stenosis. Outcomes are typically focused upon airway patency. Dysphagia is often reported in children undergoing cardiothoracic surgery, but not specifically after slide tracheoplasty. This study was carried out to describe the nature and prevalence of dysphagia following slide tracheoplasty for long segment congenital tracheal stenosis. Methods: Retrospective case note review was conducted on a series of patients who underwent swallow evaluation following slide tracheoplasty between 2006 and 2014. A clinical swallow assessment was carried out by a Speech and Language Therapist with videofluoroscopic evaluation of swallowing where indicated. Logistic regression assessed the impact of gender, feeding history, weight, tracheal diameter, stenting and co-morbidities on the likelihood of having post-operative dysphagia. Results: 43 out of 83 slide tracheoplasty patients underwent swallow evaluation. Dysphagia was identified in 30 (70%) of 43 patients. Videofluoroscopy was undertaken in 22 of these patients. All patients who had a videofluoroscopy presented with altered swallow physiology. Aspiration risk was confirmed in 15 patients with frank aspiration seen in 9. Pre-operative history of dysphagia was present in 9 patients. There were two cases of vocal fold palsy. The presence of a stent was the strongest predictor of post-operative dysphagia with an odds ratio of 10.6 (95% CI 1.2–92.8). Conclusions: This study documents a high prevalence of post-operative dysphagia in a pediatric population following slide tracheoplasty. In most cases there was no history suggestive of dysphagia pre-operatively. Swallowing needs to be assessed after slide tracheoplasty and longitudinal studies are required.